Introduction to philosophy of the human person - Bernardo, Juanito Philip V. Jr (JFS Publishing Services, 2016)
"This book is not meant though to be merely an intellectual enterprise but to arouse as well the students' interest to appreciate the beauty and wonder of the gift of life each one possesses by constantly unveiling it and share it with others to make this world a better place."--Preface.